Delving deeper into child poverty and its drivers in sub-Saharan Africa: A multidimensional approach for Nigeria - Ogunniyi, Adebayo; Mistura, Rufai; Mavrotas, George; Kehinde, Olagunju; Kabir, Salman Kayode; Fadare, Olusegun (Practical Action Publishing, 2020)
Using the 2013 Demographic Health Survey data, this chapter revisits the debate on child poverty drivers in Nigeria by employing a multidimensional poverty approach. The empirical results reveal that the poverty measures decrease with the level of dimension used. The majority of children are deprived of at least one of the basic needs. The child poverty indicators revealed that most of the under-five children in Nigeria are living below accepted standards of well-being. The situation is more prevalent in rural areas and the northern region of the country. Our findings therefore suggest that investing in the development and protection of Nigerian children is not a choice, but rather a priority. Investing in children does not mean separating out children with special needs. Instead, this requires an integrated and holistic approach supporting the communities in which children live, their basic needs, and the participatory development which will not only produce active citizens of the future but will also provide sustainable solutions to child poverty in Nigeria, a country under immense demographic pressure in the coming years.